Blunt Cardiac Injury in the Severely Injured – A Retrospective Multicentre Study - Hanschen, Marc (PLoS One, 2015)
BACKGROUND: Blunt cardiac injury is a rare trauma entity. Here, we sought to evaluate the relevance and prognostic significance of blunt cardiac injury in severely injured patients. METHODS: In a retrospective multicentre study, using data collected from 47,580 patients enrolled to TraumaRegister DGU (1993-2009), characteristics of trauma, prehospital / hospital trauma management, and outcome analysis were correlated to the severity of blunt cardiac injury. The severity of cardiac injury was assessed according to the abbreviated injury score (AIS score 1-6), the revised injury severity score (RISC) allowed comparison of expected outcome with injury severity-dependent outcome. N = 1.090 had blunt cardiac trauma (AIS 1-6) (2.3% of patients). RESULTS: Predictors of blunt cardiac injury could be identified. Sternal fractures indicate a high risk of the presence of blunt cardiac injury (AIS 0 [control]: 3.0%; AIS 1: 19.3%; AIS 2-6: 19.1%). The overall mortality rate was 13.9%, minor cardiac injury (AIS 1) and severe cardiac injury (AIS 2-6) are associated with higher rates. Severe blunt cardiac injury (AIS 4 and AIS 5-6) is associated with a higher mortality (OR 2.79 and 4.89, respectively) as compared to the predicted average mortality (OR 2.49) of the study collective. CONCLUSION: Multiple injured patients with blunt cardiac trauma are at high risk to be underestimated. Careful evaluation of trauma patients is able to predict the presence of blunt cardiac injury. The severity of blunt cardiac injury needs to be stratified according to the AIS score, as the patients’ outcome is dependent on the severity of cardiac injury.